Pengaruh Capital Adequacy Ratio, Intellectual Capital, dan Financial Non Distress Terhadap Sustainable Growth Rate pada Bank Umum Syar’iah Indonesia Periode 2020-2022 - Diautami, Novi; Atika; Nasution, Annio Indah Lestari (As-Syirkah: Islamic Economic & Financial Journal, 2024)
This research was conducted to see the effect of the influence Sustainble Growth Rate, Capital Adequacy Ratio (CAR), Intellectual Capital (IC) dan Financial Non Distress of Sharia Commersial Bank. The population used in this study is the financial statements of Sharia Commersial Bank. While the sample was taken from the financial statements of Bank Syariah Indonesia, Bank Aladin Syariah, BTPN Syariah and Bank Panin Syariah 2020 - 2022 using the sampling technique used was purposive sampling. The results of this study indicate that Capital Adequacy Ratio (CAR) has a significant effect on Sustainble Growth Rate this is based on the results of the t test - T count 0.050 then partially has a insignificant not effect between that Capital Adequacy Ratio (CAR) against Sustainble Growth Rate. Intellectual Capital (IC) has a significant effect on Sustainble Growth Rate this is based on the results of the t test - T count 0.050then partially has a insignificant not effect between that Intellectual Capital (IC) against Sustainble Growth Rate. Financial Non Distress has a significant effect on Sustainble Growth Rate this is based on the results of the t test - T count > T table or 3.673 > 1.68023, a significant value of 0. 0.001 > 0.050 then partially has a insignificant effect between that Financial Non Distress against Sustainble Growth Rate. Based on the results of the f test, the value of Fcount is greater than Ftable or 9.429 > 2.90. Then, seen from the esults, the significant value is 0.000 < 0.050. Thus Ho is accepted (Ha is rejected). Based on these results, it shows that there is a negative and insignificant effect between , Capital Adequacy Ratio (CAR), Intellectual Capital (IC) and Financial Non Distress in deciding the Sustainble Growth Rate.